Analisis Pengaruh Komunikasi dan Disiplin terhadap Kinerja Pegawai dengan Motivasi sebagai Variabel Intervening pada RSUD Rantauprapat - Mulyadi, Mulyadi; Yusuf, M; Ariska, Emalia; Zalikha, Zalikha (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to determine the effect of communication and discipline on employee performance with motivation as an intervening variable. This type of research is associative research. Data collection in this research was carried out using a survey approach with a quantitative descriptive research type by distributing questionnaires to 82 respondents, while the population used in this research were employees of Rantauprapat Regional Hospital, Labuhanbatu Regency. Data collection techniques were carried out using interviews, questionnaires and documentation studies. The data analysis tool used in this research uses SEM-PLS. The data analysis technique in this research is descriptive analysis. The results of this research show that communication on employee performance has a positive and significant effect, communication on motivation has a positive and significant effect, the influence of motivation on employee performance has a positive but not significant effect, discipline on employee performance has a positive and significant effect, discipline has an effect on motivation positively and significantly. Meanwhile, motivation does not mediate the effect of communication on employee performance. And meanwhile motivation also does not mediate the influence of work discipline on employee performance.